DUST SEPARATORS FOR PARTICULATE MATTER SEPARATION USED FOR EDUCATION PROCESS OF THE AIR PROTECTION TECHNOLOGY SUBJECT - CERNECKY, Jozef (Trends in education, 2010)
The contribution is focused to describe the filter device with continuous regeneration of the filter. This filter is one of the new separator of particulate matter. The contribution presents a scheme and calculates the main parameters of the separation process. It also describes the advantages of this type of separation in comparison with conventional filtering devices.
Keywords: separators; particulate matter; filter.